Helicopter theory - Johnson, Wayne, 1946- (Dover Publications, 1994)
Monumental text offers comprehensive, detailed coverage of every aspect of theory and design: elements of vertical flight, forward flight, performance, mathematics of rotating systems, rotary wing dynamics and aerodynamics, aeroelasticity, stability and control, more. Essential reading for those interested in design and development of vertical-flight aircraft. 189 illustrations. 1980 edition.
"This Dover edition ... is an unabridged and slightly corrected republication of the work first published by the Princeton University Press, Princeton, New Jersey, in 1980"--T.p. verso.
Keywords: Helicopters.; elektronické knihy; electronic books